Post-treatment mechanical refining as a method to improve overall sugar recovery of steam pretreated hybrid poplar. (May 2016) - Dou, Chang; Ewanick, Shannon; Bura, Renata; Gustafson, Rick
Highlights: Refining reduces the particle size of steam pretreated biomass. Refining greatly improves hydrolyzability for samples pretreated at low severity. High sugar yield is achievable with low severity, SO2 -free pretreatment via refining. Refining may mitigate process disturbances and secure stable operation of biorefinery. Abstract: This study investigates the effect of mechanical refining to improve the sugar yield from biomass processed under a wide range of steam pretreatment conditions. Hybrid poplar chips were steam pretreated using six different conditions with or without SO2 . The resulting water insoluble fractions were subjected to mechanical refining. After refining, poplar pretreated at 205 °C for 10 min without SO2 obtained a 32% improvement in enzymatic hydrolysis and achieved similar overall monomeric sugar recovery (539 kg/tonne) to samples pretreated with SO2 . Refining did not improve hydrolyzability of samples pretreated at more severe conditions, nor did it improve the overall sugar recovery. By maximizing overall sugar recovery, refining could partially decouple the pretreatment from other unit operations, and enable the use of low temperature, non-sulfur pretreatment conditions. The study demonstrates the possibility of using post-treatment refining to accommodate potential pretreatment process upsets without sacrificing sugar yields.